Factors Affecting Teaching Learning Quality at JS Murarka Multiple Campus, Lahan, Siraha (Research Journal on Multi-disciplinary Issues, 2026)
This mixed-methods study investigates factors affecting teaching–learning quality at JS Murarka Multiple Campus, Lahan, Siraha. Using surveys (n = 180 students, n = 28 teachers), semi-structured interviews with 8 administrators/teachers, and 12 classroom observations, the study identifies six principal factors: teacher professional competence, physical infrastructure and learning resources, curricular relevance, assessment practices, student engagement and socio-economic constraints, and institutional leadership/support. Quantitative analyses (exploratory factor analysis and multiple regression) showed that teacher competence and infrastructure account for the largest share of variance in perceived teaching learning quality. Qualitative findings deepened understanding of how these factors operate in context. The paper concludes with policy and practice recommendations aimed at improving classroom practice, resource allocation, professional development and leadership at JS Murarka Multiple Campus and similar institutions.